2023
DOI: 10.1007/s10198-022-01552-9
|View full text |Cite
|
Sign up to set email alerts
|

EQ-5D-5L Portuguese population norms

Abstract: Objectives The EQ-5D-5L is a generic preference-based quality-of-life measure for which the corresponding Portuguese population value set was only recently developed. This study sought to establish EQ-5D-5L population norms for Portugal and to identify significant relationships with sociodemographic variables. Methods The research was based on a representative sample of Portugal’s general population ( n = 1006) aged 18 or older. The sample was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that more than 10% of anxiety and depression are key factors affecting the quality of life of patients. 34 Therefore, psychological interventions are needed in ART clinics to improve the quality of life of HIV patients under treatment with first-line regimens. A randomized controlled trial conducted previously reported that multi-component behavioral interventions had resulted in a significant reduction in anxiety and depression within 3 months in psychologically distressed adults.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that more than 10% of anxiety and depression are key factors affecting the quality of life of patients. 34 Therefore, psychological interventions are needed in ART clinics to improve the quality of life of HIV patients under treatment with first-line regimens. A randomized controlled trial conducted previously reported that multi-component behavioral interventions had resulted in a significant reduction in anxiety and depression within 3 months in psychologically distressed adults.…”
Section: Discussionmentioning
confidence: 99%
“…The 5Q-5D-5L is a generic instrument for measuring health-related quality of life (HRQoL) based on a classification system that describes health in five dimensions: mobility, personal care, usual activities, pain/discomfort, and anxiety/depression, where each of these dimensions has five levels of severity [ 29 , 30 ]. Higher values indicate better QoL.…”
Section: Methodsmentioning
confidence: 99%
“…The internal consistency, measured by the Cronbach α coefficient, was 0.836 (0.750–0.900). The second part of the EQ-ED-5L, called EQ-VAS, measures the health status, recorded in a continuous quantitative scale ranging from 0 (worst imaginable health status) to 100 (best imaginable health status) [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…A visual analogue scale also asks for self-perception of general health status. Portuguese utilities can be computed by an algorithm based on general public preferences [ 30 ] and Portuguese norms are also available [ 31 ].…”
Section: Methodsmentioning
confidence: 99%